2023
DOI: 10.3390/jof9060658
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Diversity of Candida auris, Candida blankii, and Kodamaea ohmeri Isolated from Septicemia and Otomycosis in Bangladesh as Determined by Multilocus Sequence Typing

Abstract: Candida auris, Candida blankii, and Kodamaea ohmeri have been regarded as emerging fungal pathogens that can cause infections with high mortality. For genotyping of C. auris, a multilocus sequence typing (MLST) scheme based on four locus sequences has been reported, while there is no typing scheme for C. blankii and K. ohmeri. In the present study, the existing MLST scheme of C. auris was modified by adding more locus types deduced from sequence data available in the GenBank database. Furthermore, MLST schemes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
(86 reference statements)
0
4
0
Order By: Relevance
“…Wound and soft tissue infections, osteomyelitis, central nervous system infections, and generalized infections in immunosuppressed patients have been described in the international literature [ 60 ]. According to our systematic review, we located 24 publications [ 23 , 24 , 25 , 32 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ] from 2013 until today, in which 476 cases of C. auris infections are reported. Unfortunately, there was a lot of information missing among the retrieved studies.…”
Section: Discussionmentioning
confidence: 99%
“…Wound and soft tissue infections, osteomyelitis, central nervous system infections, and generalized infections in immunosuppressed patients have been described in the international literature [ 60 ]. According to our systematic review, we located 24 publications [ 23 , 24 , 25 , 32 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ] from 2013 until today, in which 476 cases of C. auris infections are reported. Unfortunately, there was a lot of information missing among the retrieved studies.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings, along with the existing genomic data, suggest that the genetic diversity of this emerging species is restricted. In contrast, one study used a Multi-Locus Sequence Typing (MLST) approach with six K. ohmeri isolates causing infections in Bangladesh, and the authors reported five different allelic profiles [ 43 ]. The authors present a dendrogram displaying eight distinct clusters.…”
Section: Discussionmentioning
confidence: 99%
“…K.ohmeri is considered to be an emerging and rare fungal pathogen that can cause invasive infections such as peritonitis, endocarditis, urinary tract infection, ear infection, cellulitis, fungemia, tinea onychomycosis, pneumonia, keratitis, oral diseases, and disseminated infections, with high mortality rates due to fungal bacteraemia, especially in children [1][2][3] Molecular epidemiological information on K. ohmeri isolates is currently unavailable, and studies have speculated that their wide range of infection types may be related to the underlying genomic diversity that allows K. ohmeri to adapt to a variety of human sites and tissues [4] . This microbe has been found in patients around the world, with nearly 70% of infections occurring in Asia (especially East and Southeast Asia), but its regional and ethnic heterogeneity is unknown due to the low number of reported cases.…”
Section: Discussionmentioning
confidence: 99%